Wealth Distribution in Islam: The Role of Sharia Instruments in Improving Social Welfare - Aisyah, Aisyah; Arsyadi, Baso; Wahab, Abdul; Lutfi, Mukhtar (YASIN, 2025)
This study aims to analyze the role of distribution in Islamic economics as a mechanism for creating social justice and social welfare. The researchers use a qualitative approach with a descriptive-analytical method based on a literature review of relevant primary and secondary sources. The study results indicate that distribution in Islamic economics is central to reducing the gap between the rich and the poor. The principle of justice that underlies this system gives every individual the right to get a decent opportunity to improve their lives. Instruments such as zakat, infaq, sedekah, and waqf function as a means of redistributing wealth, thus ensuring that wealth is accumulated in certain groups and continues to circulate and benefit the wider community. In addition, the distribution of wealth in Islam not only focuses on material welfare but also strengthens social solidarity and the unity of the people.